KAJIAN ETNOBOTANI PANDAN SAMAK (Pandanus tectorius Sol.) DIKABUPATEN TASIKMALAYA, JAWA BARAT - Susiarti, Siti; Rahayu, Mulyati (BERITA BIOLOGI, 2010)
Members of the genus Pandanus (Pandanaceae) are used by Indonesian people as food, medicinal and handycraft materials.Three species of Pandanus, namely pandan wangi (P. amaryllifolius), cangkuang (P. furcatus) and pandan samak (P. tectorius) are known in Tasikmalaya, West Java. Pandan samak which has several different local names is the cultivated ones.This species is well known as handycraft from Tasikmalaya and had been exported to other countries. Incomes from the handycraft products is the second biggest source after agricultural sector.